The United Kingdom’s Policy towards the First Post-war Integration Initiatives of Western Europe and the USA (Economic and Political Thought, 2010)
The article discusses the United Kingdom’s policy towards the first postwarintegration initiatives of Western Europe and the United States. Theinitiators and authors of projects to unite Europe were various politicalorganizations of Western Europe and the government of the United States.The United Kingdom was a world superpower at that time and because ofvarious reasons it had to take an ambivalent stand on the issue of WesternEuropean integration. On account of the specificity of its internationalinterests, which are thoroughly analyzed by the author, this state could notactively participate in the European integration trend. However, it was not inthe British interest to sabotage the integration undertakings of the continentalpart of Western Europe either. In such circumstances, the United Kingdomforced through a policy of close co-operation between Western Europeancountries as an alternative to integration ideas.Until 1954 the British policy towards continental integration initiativescan be described as very effective. The United Kingdom skillfully managedto hold up the use of post-war American aid to Europe as a form of stimulusfor Western European integration (European Recovery Program – MarshallPlan). As a result of its policy, an authentically European parliamentaryassembly, aimed at initiating and stimulating European integration processthrough grass-roots social pressure on governments (Resolution of theHague Congress), did not take place. The political and diplomatic successesdetermined the British assessment of prospects for the European integrationand British possibilities to influence the process of Western Europeanunification. They made British politicians incorrectly – as it turned out – believethat the United Kingdom could successfully halt attempts of supranationalintegration by forcing through an idea of co-operation of sovereign states.After a few years there were no doubts that the assessment had been wrong.In this case traditional attitude towards international politics did badly incomparison with new realities, i.e. an innovative integration trend.